Challenges and Strategies Using Application in Teaching Online Classroom During Pandemic Covid-19 - Fransiska M. Ena Tukan (ELITE JOURNAL, 2020)
This paper aimed to find out (1) the teacher’s challenges using the application in teaching online classrooms during pandemic COVID-19, and (2) the strategies used by teachers in teaching using the application. The participants of the research were the English teachers at SMA/SMK/MA in Yogyakarta, Gunungkidul, Magelang, and Kebumen. A qualitative method was employed in this research and using interview via WhatsApp as data collection. The findings showed that teachers had the challenges such as (1) operating the application during online learning, (2) developing the material, assessment, and evaluation in teaching, (3) developing the teaching method, (4) combining the material and application, and (5) motivating the students and parents. The strategies used by the teacher when using the application in teaching such as (1) watching the video tutorial, (2) choosing a suitable application for teaching, (3) arranging the new learning schedule, (4) developing the creativity in designing the material, and (5) giving the simple material and task for the students.